ঢাকা পুরাণ - রহমান, মীজানুর, ১৯৩১-২০০৬. (ঢাকা : প্রথমা প্রকাশন, 2013)
Autobiographical reminiscences of Mījānura Rahamāna, 1931-2006, editor of a Bengali journal and author, chiefly on Dhaka city, Bangladesh.
Donated By Akbar Ali Khan
Keywords: Dhaka (Bangladesh) -- History; Dhaka (Bangladesh) -- Biography